mRNA fate: Life and death of the mRNA in the cytoplasm - Denti, Michela A. (Landes Bioscience, 2013)
The life of an mRNA molecule begins with transcription and ultimately ends in degradation. In the course of its life, however, mRNA is examined, modified in various ways and transported before eventually being translated into proteins. All these processes are performed by proteins and non-coding RNAs whose complex interplay in the cell contributes to determining the proteome changes and the phenotype of cells. On May 23‒26, 2012, over 150 scientists from around the world convened in the sunny shores of Riva del Garda, Italy, for the workshop entitled: “mRNA fate: Life and Death of mRNA in the Cytoplasm.” Sessions included mRNA trafficking, mRNA translational control, RNA metabolism and disease, RNA-protein structures and systems biology of RNA. This report highlights some of the prominent and recurring themes at the meeting and emerging arenas of future research.